Adsorption of Nitenpyram and Acetamiprid on Modified Resin with Proline - Wu, Xiuhong; Zhang, Xuehua; Zhang, Hongmei; Zhang, Gencheng; Fei, Zhenghao (Asian Journal of Chemistry, 2013)
The adsorption behaviour of nitenpyram and acetamiprid in water onto the resin modified with proline based was investigated by static adsorption experiments at different temperature (288, 303 and 318 K) in single component and binary components system. The adsorption capacities and adsorption selectivity for acetamiprid in water were tested. The results showed the adsorption was fitted better by Freundlich model than Langmuir model in single system. The adsorption of nitenpyram on the resin modified with proline was an endothermic process by the positive adsorption enthalpy and an exothermic process of acetamiprid with the negative adsorption enthalpy. Entropy change was giving a friendly boost to adsorption. The resin had better absorbability for acetamiprid than for nitenpyram and the adsorption selectivity of acetamiprid was larger than one at lower temperature as well as at lower concentrations. A high removal rate of 45.56-82.66 % was obtained for nitenpyram studied and the removal rate of acetamiprid was in the range of 48.77-86.23 % in single component system. In binary components system the removal rate of acetamiprid was higher, lower for nitenpyram, because of competition in adsorption site. The equilibrium adsorption isotherms of both nitenpyram and acetamiprid in binary components system were fitted better by Langmuir model. So the adsorption of nitenpyram and acetamiprid on the resin modified with proline was on the monolayer adsorption in binary components system. But the cooperative effect existed at 318 K. In additional studies, the competitive adsorption existed. The adsorption of acetamiprid onto the resin had just smaller change in the presence of nitenpyram, but the adsorption of nitenpyram was weakened obviously in the presence of acetamiprid. The adsorption selectivity of acetamiprid on the resin is larger than one on lower temperature with lower concentrations.